2015
DOI: 10.1007/s11270-015-2672-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a Methanogenic Consortium to Arsenite Inhibition

Abstract: Arsenic (As) is a ubiquitous metalloid known for its adverse effects to human health. Microorganisms are also impacted by As toxicity, including methanogenic archaea, which can affect the performance of process in which biological activity is required (i.e. stabilization of activated sludge in wastewater treatment plants). The novel ability of a mixed methanogenic granular sludge consortium to adapt to the inhibitory effect of arsenic (As) was investigated by exposing the culture to approximately 0.92 mM of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The IC 50 value calculated for both As(III) and As(V) in this bioassay was about 0.02 mM. The inhibition results obtained for As (III) are in close agreement with those reported in a previous study using a similar experimental protocol (Rodriguez-Freire et al, 2015). On the other hand, the acetoclastic methanogens in the inoculum utilized in this study were more sensitive to As(V) than previously reported by Sierra-Alvarez and coworkers for a methanogenic mixed culture (IC 50 > 0.50 mM) (Sierra-Alvarez et al, 2004).…”
Section: Microtox Acute Toxicity Bioassaysupporting
confidence: 91%
“…The IC 50 value calculated for both As(III) and As(V) in this bioassay was about 0.02 mM. The inhibition results obtained for As (III) are in close agreement with those reported in a previous study using a similar experimental protocol (Rodriguez-Freire et al, 2015). On the other hand, the acetoclastic methanogens in the inoculum utilized in this study were more sensitive to As(V) than previously reported by Sierra-Alvarez and coworkers for a methanogenic mixed culture (IC 50 > 0.50 mM) (Sierra-Alvarez et al, 2004).…”
Section: Microtox Acute Toxicity Bioassaysupporting
confidence: 91%
“…Although a high degree of correlation does not confirm causality, these findings are in agreement with the published literature. Arsenic can be highly inhibitory, depending on its form, with trivalent forms having 50% inhibitory concentrations of 0.7 and 1.1 mg L −1 ; nonetheless, there have been few studies on the effect of arsenic on AD [146,147] and especially seaweed. However, the highest concentration of total arsenic in the reactors for this study was 0.6 mg L −1 below the 50% inhibitory concentration of the trivalent form of arsenic, and thus, the levels of arsenic, although potentially concerning, may not be inhibitory for methane production.…”
Section: Methane Potential Of S Natans VIII S Natans I S Fluitanmentioning
confidence: 99%